Program Kemitraan Masyarakat Pelatihan Biopori Untuk Konservasi Air Tanah Di Desa Warembungan Minahasa: Community Partnership Program For Biopore Training And Groundwater Conservation In Warembungan Village Minahasa (Tumou Tou: Jurnal Pengabdian Masyarakat, 2025)
Warembungan Village experiences seasonal water scarcity despite relatively high rainfall, mainly due to low groundwater infiltration and limited community awareness of groundwater conservation. This Community Partnership Program aimed to improve community knowledge and skills in implementing biopore technology as a simple and sustainable approach to drought mitigation. The program was conducted through community outreach, technical training, hands-on practice, and mentoring in biopore construction and maintenance. The results indicate a significant increase in participants’ understanding of groundwater conservation concepts and their ability to construct biopores independently. The implementation of biopores also encouraged the utilization of household organic waste as compost material, contributing to environmental management. Overall, the program demonstrated that biopore-based community empowerment can enhance groundwater recharge capacity and strengthen local resilience to drought conditions. This approach has strong potential for replication in other drought-prone areas with similar environmental characteristic